2019
DOI: 10.3390/ijerph16214079
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum TNF-α Levels and Blood Multi-Elements Modified by TNF-α Gene Polymorphisms in Metal Industrial Workers

Abstract: Health of the metal industrial workers should be a noteworthy issue due to the hazard of chronic exposure to metals or toxic elements. The interactions among multiple elements are sophisticated and may differ from person to person. Tumor necrosis factor-α (TNF-α) gene polymorphisms were supposed to be involved with the interactions because TNF-α plays an important role in inflammation, a mechanism by which toxic elements cause threats to human health. This research aimed to analyze the influence of TNF-α gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Data on how rs1800630 affects TNF gene expression levels in the hippocampus taken from the eQTL database were consistent with the previously mentioned findings in the existing literature in that the C allele upregulates TNFα ( Chen et al., 2019 ) in comparison to the homozygous genotype including the alternative allele.…”
Section: Variants With Demonstrated Associations With the Risk Of Neurological Or Psychiatric Diseasessupporting
confidence: 87%
See 2 more Smart Citations
“…Data on how rs1800630 affects TNF gene expression levels in the hippocampus taken from the eQTL database were consistent with the previously mentioned findings in the existing literature in that the C allele upregulates TNFα ( Chen et al., 2019 ) in comparison to the homozygous genotype including the alternative allele.…”
Section: Variants With Demonstrated Associations With the Risk Of Neurological Or Psychiatric Diseasessupporting
confidence: 87%
“…(2012) C allele was associated with COX2 overexpression by disrupting micro-RNA-mediated mRNA degradation (not replicated by Piranda et al. (2017) ) rs1800630 (= -863C/A) TNF = LTA Chronic inflammatory response, neurogenesis CC (homozygous reference) Chen et al. (2019) CC genotype was associated with higher serum TNFα levels Higuchi et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the mechanism, Ma et al demonstrated that there was a positive correlation between urinary Cu and plasma C-reactive protein (CRP) [ 28 ] and that CRP was associated with MetS [ 38 ]. Furthermore, our previous research showed that blood Cu concentration was positively associated with serum TNF-α [ 39 ]. We proposed that the association of Cu exposure with MetS may be on the basis of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, metalworkers are exposed to a wide range of compounds, such as heavy metals, solvents, and metalworking fluids (MWF), that can negatively affect their health (Fornander et al, 2013;Hopf et al, 2019). Metals such as lead, cadmium, arsenic, and manganese are commonly related to metallurgy and are recognized as agents that can damage many target organs in the human body (Chen et al, 2019). In addition, a study conducted by Hamzah et al (2016) showed that cobalt and chromium levels were above the allowed exposure limit and that they were related to decreased lung function in workers exposed.…”
Section: Introductionmentioning
confidence: 99%